Novel TONSL variants cause SPONASTRIME dysplasia and associate with spontaneous chromosome breaks, defective cell proliferation and apoptosis. (21st September 2020) - Micale, Lucia; Cialfi, Samantha; Fusco, Carmela; Cinque, Luigia; Castellana, Stefano; Biagini, Tommaso; Talora, Claudio; Notarangelo, Angelantonio; Bisceglia, Luigi; Taruscio, Domenica; Salvatore, Marco; Castori, Marco
Abstract: SPONASTRIME dysplasia is an ultrarare spondyloepimetaphyseal dysplasia featuring short stature and short limbs, platyspondyly, depressed nasal bridge with midface hypoplasia and striated metaphyses. In 2019, an autosomal recessive inheritance was demonstrated by the identification of bi-allelic hypomorphic alleles in TONSL . The encoded protein has a critical role in maintaining genome integrity by promoting the homologous recombination required for repairing spontaneous replication-associated DNA lesions at collapsed replication forks. We report a 9-year-old girl with typical SPONASTRIME dysplasia and resulted in carrier of the novel missense p.(Gln430Arg) and p.(Leu1090Arg) variants in TONSL at whole-exome sequencing. In silico analysis predicted that these variants induced thermodynamic changes with a pathogenic impact on protein function. To support the pathogenicity of the identified variants, cytogenetic analysis and microscopy assays showed that patient-derived fibroblasts exhibited spontaneous chromosomal breaks and flow cytometry demonstrated defects in cell proliferation and enhanced apoptosis. These findings contribute to our understanding of the molecular pathogenesis of SPONASTRIME dysplasia and might open the way to novel therapeutic approaches. Graphical Abstract: